2020
DOI: 10.1161/atvbaha.120.314139
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Inhibition of Gut Microbial Trimethylamine N-Oxide Production Reduces Renal Tubulointerstitial Fibrosis and Functional Impairment in a Murine Model of Chronic Kidney Disease

Abstract: Objective: Gut microbial metabolism of dietary choline, a nutrient abundant in a Western diet, produces trimethylamine (TMA) and the atherothrombosis- and fibrosis-promoting metabolite TMA-N-oxide (TMAO). Recent clinical and animal studies reveal that elevated TMAO levels are associated with heightened risks for both cardiovascular disease and incident chronic kidney disease development. Despite this, studies focusing on therapeutically targeting gut microbiota-dependent TMAO production and its imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 124 publications
(113 citation statements)
references
References 77 publications
9
101
1
2
Order By: Relevance
“…Our results tie well with those of previous studies demonstrating that alterations of specific gut microbial composition and metabolites have an essential role in hypertension development [ 9 , 10 ]. Given that inhibition of the TMA-TMAO metabolic pathway has been reported to protect adult offspring against hypertension programmed by early life insult and CKD progression [ 31 , 32 , 33 ], outcomes from targeting the TMA-TMAO pathway to protect against CKD-related adverse pregnancy and offspring need further research.…”
Section: Discussionmentioning
confidence: 99%
“…Our results tie well with those of previous studies demonstrating that alterations of specific gut microbial composition and metabolites have an essential role in hypertension development [ 9 , 10 ]. Given that inhibition of the TMA-TMAO metabolic pathway has been reported to protect adult offspring against hypertension programmed by early life insult and CKD progression [ 31 , 32 , 33 ], outcomes from targeting the TMA-TMAO pathway to protect against CKD-related adverse pregnancy and offspring need further research.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic approaches have emerged for reducing TMAO levels, including the use of prebiotics, probiotics, and antibiotics to elicit a favorable impact on gut microbiota, 3,3-dimethyl-1-butanol or iodomethylcholine by suppressing the activity of microbial choline trimethylamine (TMA) lyase 5,10) , and diet modification to reduce the intake of choline and carnitine Trimethylamine (TMA) is generated from choline (derived from egg, shrimp, and milk); betaine (vegetable and mushroom); and carnitine (red meat) by three specific TMA lyases; namely, choline TMA lyase, betaine reductase, and carnitine monooxygenase, respectively. Produced TMA is metabolized by liver host enzyme and is changed to TMAO.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Studies have shown that TMAO is independently related to cardiovascular events and that a relationship between TMAO levels and ischemic cardiovascular events exists, especially in CKD Stages 3b and 4 [ 30 ]. For these reasons, selective inhibition of TMAO prevents renal damage and cardiovascular events in patients with CKD [ 31 ].…”
Section: Effect Of Nontraditional Risk Factors (Uremic Toxins) On mentioning
confidence: 99%